Giving less by doing more?: dynamics of social policy expansion and dismantling in 18 OECD countries - Jensen, Carsten; Knill, Christoph; Schulze, Kai; Tosun, Jale (Journal of European public policy, 2014)
Protection against social risks is generally popular among voters and should enjoy the benefits of institutional inertia. Yet retrenchment occurs rather frequently in advanced welfare states without this systematically leading to electoral punishment. We solve this paradox by, first, arguing that governments can avoid the blame of retrenchment by pursuing a strategy of ‘expansionary dismantling’ where new policies and instruments are used to compensate reform losers and to obfuscate cutbacks. Second, we test our argument with a huge new dataset consisting of changes in unemployment legislation and replacement rates in 18 OECD countries from 1976 to 2000. The statistical tests provide robust support for our argument, suggesting that the introduction of new policies and instruments leads to cutbacks in replacement rates. We also find that left-leaning governments are least likely to engage13 Jan 2014 in expansionary dismantling.
Gesehen am 08.09.2020